Komunikasi Mitigasi Bencana Pada Peserta Didik Sekolah Dasar - Siregar, Mariana Rista Ananda; Sariswara, Valianty; Nuraisyiah, Siti Fathonah (Universitas Djuanda Bogor, 2025)
This study aims to analyze the disaster mitigation communication steps implemented by the Citeko Meteorological Station of BMKG through the